RELIGIUSITAS MAHASISWA PERBANKAN SYARIAH S1 UIN MALANG YANG MENGGUNAKAN JASA BANK SYARIAH - Mohammad Dendi Abdul Nasir (JURNAL EKONOMI SYARIAH, 2020)
Religiousity is an expression of embraced system of trust that feels its values, so it created an option to react and behave in decision making. Islamic bank is a bank implements Islamic values which are arranged in Fatwa Dewan Syariah Nasional. In Islamic banking world, religiousity is one of many factors for customers to choose Islamic bank to save their money on. This research aims to discover how much is religiosity of students which are also costumers of Islamic bank.This is a qualitative research. Subjects for this research are 7 students which are customers of Islamic bank. This research uses primary and secondary data. Primary data is taken from interview with subjects and secondary data taken from older researches and theory books.This research shows that students religiosity which are costumers of Islamic bank is great. This is proven by metering five dimensions of religiousity, which are dimension of ideology, dimension of rituality, experience dimension, dimension of intellectuality, and consequence dimension.Keywords: Religiousity, Islamic Bank.